2018
DOI: 10.1177/0269216318800610
|View full text |Cite
|
Sign up to set email alerts
|

Quality of dying and quality of end-of-life care of nursing home residents in six countries: An epidemiological study

Abstract: Background:Nursing homes are among the most common places of death in many countries.Aim:To determine the quality of dying and end-of-life care of nursing home residents in six European countries.Design:Epidemiological survey in a proportionally stratified random sample of nursing homes. We identified all deaths of residents of the preceding 3-month period. Main outcomes: quality of dying in the last week of life (measured using End-of-Life in Dementia Scales – Comfort Assessment while Dying (EOLD-CAD)); quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 38 publications
(68 reference statements)
1
97
0
2
Order By: Relevance
“…The main limitation of this analysis that the PACE study was developed to compare the outcomes, quality and costs of palliative and end-of-life care between countries 22. Consequently, much of the data collected were related to either the last month or week of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of this analysis that the PACE study was developed to compare the outcomes, quality and costs of palliative and end-of-life care between countries 22. Consequently, much of the data collected were related to either the last month or week of life.…”
Section: Discussionmentioning
confidence: 99%
“…In England, LTCFs were also recruited from Enabling Research in Care Homes, a network of LTCFs with an interest in research participation 20. The methods used to recruit the LTCF and ethical approvals are discussed in the study protocol and primary outcomes publication 21 22…”
Section: Methodsmentioning
confidence: 99%
“…22 Moreover, EDs are not the most appropriate place for dying. 12 It has been found that the quality of end-of-life care and quality of dying of nursing home residents were insufficient in Europe, 23 even though the number of deaths in nursing homes is growing in many countries worldwide. 24,25 If additional palliative care guidelines and practice tools are needed to improve quality of dying nursing home residents, ED should not be a solution for dying.…”
Section: Discussionmentioning
confidence: 99%
“…5,12 This is compounded by a workforce that is under-resourced (70% of direct RAC workers are personal care attendants 13 ), lacking in palliative care knowledge and skills, and access to suitably experienced and skilled specialist palliative care clinicians. 14,15 These barriers are greatest in rural locations due to distance that restricts access to services, training and mentoring, 14,16 and lack of equity of service provision between rural and city areas. 17 For example, in 2017, the national full-time equivalent (FTE) for employed palliative care nurses per 100 000 population was 12.0 FTE in major cities, dropping to 9.7 in outer regional areas, 5.0 in remote areas and 1.9 in very remote areas; the FTE for employed palliative medicine physicians was 1.1, 0.7, 0 and 0, respectively.…”
Section: Introductionmentioning
confidence: 99%